Synthetic approaches to N- and 4-substituted 1, 4-dihydro-3(2H)-isoquinolinone derivatives. (5th November 2021) - O' Sullivan, Michael J.; Hatley, Richard J.D.; Wellaway, Christopher R.; Bew, Sean P.; Richards, Christopher J.
Abstract: Reaction of methyl-2-(2-formylphenyl)acetate with primary amines in a reductive amination/cyclisation process resulted in N -substituted 1, 4-dihydro-3(2H)-isoquinolinones. With H2 NCH2 R sodium borohyride is a suitable reductant (11 examples), but H2 NCHR 1 R 2 required a transfer hydrogenation using ammonium formate catalysed by palladium on carbon (9 examples). 4-Substituted-1, 4-dihydro-3(2H)-isoquinolinones were synthesised by deprotonation ( n -butyllithium) and addition of R 3 CH2 Br (12 examples with R 3 = alkyl, Ar, CHCH2, CCH). Modest diastereoselectivity was achieved with 1, 4-dihydro-3(2H)-isoquinolinones derived from H2 NCHMeR 2 [R 2 = (η 5 -C5 H4 )Co(η 4 -C4 Ph4 ) - max. dr = 1.9 : 1], but use of H2 NCHMeFc (Fc = ferrocenyl) provided a new method of 1, 4-dihydro-3(2H)-isoquinolinone N -deprotection with formic acid. Graphical abstract: Image 1